Crisis Prevention and Management: What Worked in the 2008/2009 Crisis? - Torbjörn Becker (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
This paper takes a systematic look at the economic impact of the crisis that started in earnest in the fall of 2008 across countries and regions. Despite warnings of growing domestic and external imbalances in many countries years ahead of the crisis, the massive impact of the crisis came as a surprise to most. By correlating economic performance in the crisis with an extensive set of early warning, country insurance, and policy indicators, this paper provides some lessons on crisis prevention and management for the future. Although significant efforts have been made to develop robust early warnings systems, the paper shows the mixed success of some commonly analyzed indicators in predicting economic outcomes in this crisis. The only robust early warning indicator was increases in real estate prices while international reserves seem to have insured against the worst crisis outcomes on average. However, much work on building a robust early warning system remains and the analytical and empirical challenges in this area are substantial. The issues confronting early warning systems are also relevant to the more recent field of macro prudential supervision and regulation. Nevertheless, the cost of crises is massive and preventing future ones with better regulation, policies and supervision based on solid research must be a top priority among policy makers and academics alike.
Keywords: E66; 330; Economic crisis; crisis prevention; early warning indicators